ENRICHMENT FACTORS OF HEAVY METALS IN IRON - MANGANESE CONCRETIONS FROM IMPERFECTLY DRAINED SOILS - Γασπαράτος Δ.; Χαϊντούτη Κ.; Ταρενίδης Δ.; Τσαγκαλίδης Α. (Bulletin of the Geological Society of Greece, 2004)
The Fe-Mn concretions are morphological features of soils under alternating oxidizing and reducing conditions. They have a high adsorption capacity for many inorganic pollutants, like heavy metals. This study determines the enrichment factors of Fe, Μη, Ni, Co, Pb and Cd in Fe-Mn concretions collected from imperfectly -drained soils in Central Greece. The data show that the concretions absorbed significant amounts of heavy metals and especially of lead and cadmium from the soil system. According to the enrichment factors, the affinity of heavy metals for the concretions due to the charged surfaces of iron and manganese oxides, follow the order Pb>Cd>Mn>Co>Ni>Fe. McKenzie (1980) also found adsorption of cobalt, manganese, nickel and lead at the same order on nine synthetic manganese oxides while Nimfopoulos et al. (1997) showed that the mobility of the metals at karst cavities enriched with Mn oxides followed the order Na>K>Mg>Sr>Mn>As>Zn>Ba>AI>Fe>Cu>Cd>Pb.